2017
DOI: 10.1007/s00256-017-2615-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) uptake in tuberculous compared to bacterial spondylodiscitis

Abstract: Higher SUV levels at FDG-PET were detected in tuberculous compared with pyogenic spondylodiscitis. PET-CT use appeared useful in the disease follow-up after treatment initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…In this setting, imaging represents a key diagnostic tool to achieve early diagnosis of the disease and to monitor the response to antibiotic treatment. As observed previously (Bassetti et al, 2017), the association of specific FDG-PET/CT features, such as high SUV, with tubercular VO has been reported but remains to be determined definitively (Bakheet et al, 1998;Trecarichi et al, 2012). Then, the confirmation of high SUV values could allow physicians to consider a tubercular etiology for VO in a more timely manner (Heysell et al, 2013).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this setting, imaging represents a key diagnostic tool to achieve early diagnosis of the disease and to monitor the response to antibiotic treatment. As observed previously (Bassetti et al, 2017), the association of specific FDG-PET/CT features, such as high SUV, with tubercular VO has been reported but remains to be determined definitively (Bakheet et al, 1998;Trecarichi et al, 2012). Then, the confirmation of high SUV values could allow physicians to consider a tubercular etiology for VO in a more timely manner (Heysell et al, 2013).…”
Section: Discussionmentioning
confidence: 79%
“…In this study population, failure of therapy for VO was observed in 19 patients (14.3%). The failure rate of patients treated for VO in most clinical studies has varied between 10% and 30% (Berbari et al, 2015;Ohtori et al, 2010;Hungenbach et al, 2013;Sehn and Gilula, 2012;Bhavan et al, 2010;Saeed et al, 2019;Kowalski et al, 2007;Zarrouk et al, 2007;Carragee, 1997;Nanni et al, 2012;Kim et al, 2009;Bassetti et al, 2017;Bakheet et al, 1998;Trecarichi et al, 2012;Heysell et al, 2013;Rissing, 1997). The therapeutic management of VO patients with treatment failure should be tailored to the suspected reason for failure.…”
Section: Discussionmentioning
confidence: 99%
“…involved, with some data showing different uptake values according with the etiology of infection [13]. Specifically, higher uptake values have been reported in tuberculous spondylodiscitis compared with pyogenic one [17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In mycobacterial vertebral osteomyelitis higher uptakes levels at FDG-PET were detected in in comparison with pyogenic spondylodiscitis. PET-CT use appeared useful in the disease follow-up after treatment initiation to guide duration [17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Imaging-guide vertebral biopsy is a gold standard for differentiating tubercular and pyogenic spondylodiscitis. MRI and 18 F-FDG PET/CT were helpful for evaluating the extension of the infection [35]. The main MRI findings, suggestive for tubercular spondylodiscitis, indicated sparing of the intervertebral disc in the early stages of infection, loss of vertebral body cortical definition, multiple vertebral involvement, and the presence of muscular (paraspinal, psoas) abscesses [34,35].…”
Section: Discussionmentioning
confidence: 99%